High temperature performance of wire-arc additive manufactured Inconel 718 - James, William Sean; Ganguly, Supriyo; Rodrigues Pardal, Goncalo (Springer, 2023)
In developing a wire-arc directed energy deposition process for superalloys used in high-speed flight environments, Inconel 718 was deposited using a plasma arc process and tested for its high temperature performance. The deposited material was tested in both the as deposited condition and after an age-hardening industry standard heat-treatment for this alloy. Results showed a reduced performance in both deposited conditions, with heat-treated material significantly outperforming as deposited material up to 538 °C. The difference in performance was less significant from 760 to 1000 °C, owing to an in-test aging process which increased the performance of the as deposited material. The microstructure of deposited material showed significant cracking throughout the alloy and formation of secondary phases throughout the matrix, with significantly more precipitation after heat-treating.